The essence of professional orientation of future specialists in the automobile and road construction industry - Razumovska, N. (Problems of Engineer-Pedagogical Education, 2018)
The article reviews the essence of professional orientation of future specialists in the automobile and road construction industry. It is emphasized that the process of training specialists in the automobile and road construction industry is one of the topical issues which attract close attention of the scientists who conduct research into the development of a new generation of professionals within the system of continuing education – lifelong education. The researcher suggests considering professional orientation as an integral (comprehensive) quality of an individual that is a hierarchically organized system of professionally relevant motives, interests and values that determine a selective attitude to the profession, success in mastering relevant professional skills and knowledge, etc. The article analyzes the concept of "personal orientation". N. Razumovska claims that orientation is a pivotal and multifaceted quality of a human being, resulting in his or her originality and individuality, and is an alloy of motives, interests, needs, aptitudes and aspirations of an individual, as well as of his or her ideals and beliefs that condition his or her self-perception, inner position and personal attitude to the world.